Topsoil organic matter build‐up in glacier forelands around the world. (16th January 2021) - Khedim, Norine; Cécillon, Lauric; Poulenard, Jérôme; Barré, Pierre; Baudin, François; Marta, Silvio; Rabatel, Antoine; Dentant, Cédric; Cauvy‐Fraunié, Sophie; Anthelme, Fabien; Gielly, Ludovic; Ambrosini, Roberto; et al.
Abstract: Since the last glacial maximum, soil formation related to ice‐cover shrinkage has been one major sink of carbon accumulating as soil organic matter (SOM), a phenomenon accelerated by the ongoing global warming. In recently deglacierized forelands, processes of SOM accumulation, including those that control carbon and nitrogen sequestration rates and biogeochemical stability of newly sequestered carbon, remain poorly understood. Here, we investigate the build‐up of SOM during the initial stages (up to 410 years) of topsoil development in 10 glacier forelands distributed on four continents. We test whether the net accumulation of SOM on glacier forelands (i) depends on the time since deglacierization and local climatic conditions (temperature and precipitation); (ii) is accompanied by a decrease in its stability and (iii) is mostly due to an increasing contribution of organic matter from plant origin. We measured total SOM concentration (carbon, nitrogen), its relative hydrogen/oxygen enrichment, stable isotopic ( 13 C, 15 N) and carbon functional groups (C‐H, C=O, C=C) compositions, and its distribution in carbon pools of different thermal stability. We show that SOM content increases with time and is faster on forelands experiencing warmer climates. The build‐up of SOM pools shows consistent trends across the studied soil chronosequences. During the first decades of soil development, the low amount of SOM is dominated by a thermally stable carbon pool with a small and highly thermolabile pool. The stability of SOM decreases with soil age at all sites, indicating that SOM storage is dominated by the accumulation of labile SOM during the first centuries of soil development, and suggesting plant carbon inputs to soil (SOM depleted in nitrogen, enriched in hydrogen and in aromatic carbon). Our findings highlight the potential vulnerability of SOM stocks from proglacial areas to decomposition and suggest that their durability largely depends on the relative contribution of carbon inputs from plants. Abstract : In glacier forelands all over the world, the organic matter build‐up during the initial stages of topsoil development is strongly modulated by climate: a warmer climate accelerates accumulation of organic matter. We also detected a decreasing thermal stability of soil organic matter along the chronosequences. The observed changes in soil organic matter elemental stoichiometry, aromaticity and stable isotope signature with soil organic matter accumulation suggest an increasing contribution of organic matter from plant origin during the first centuries of topsoil development.